2012
DOI: 10.3378/027.084.0405
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Susceptibility to Type 2 Diabetes: A Global Meta-Analysis Studying the Genetic Differences in Tunisian Populations

Abstract: The present study is the first meta-analysis to evaluate type 2 diabetes (T2D) -associated polymorphisms in cohorts originated from several Tunisian regions. In fact, we evaluated the effect of seven polymorphisms in the following genes ; PPARg ( Pro12Ala), TNFα (-308A/G), ENPP1(K121Q), TCF7L2(rs7903146 C/T), MTHFR( C677T), ACE(I/D), CAPN10(3R/2R) on T2D risk, through a meta-analysis combining data of previous studies performed on Tunisian populations originating from the north, centre or south of the country.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 39 publications
2
12
0
Order By: Relevance
“…First, we cannot rule out the possibility of population stratification bias when analyzing our samples, even though only white subjects were studied and both T2DM patients and non-diabetic subjects were recruited from the same hospital, thus reducing the risk of false-positive/negative associations due to this bias. Second, we did not perform a replication of the observed association in another sample from Southern Brazil, although our data is in agreement with the majority of studies performed in different populations (5)(6)(7)(8)31,(36)(37)(38)(39)(40) and also with another Brazilian study (23). Third, we only analyzed one SNP in the TCF7L2 gene.…”
Section: Discussionsupporting
confidence: 41%
See 1 more Smart Citation
“…First, we cannot rule out the possibility of population stratification bias when analyzing our samples, even though only white subjects were studied and both T2DM patients and non-diabetic subjects were recruited from the same hospital, thus reducing the risk of false-positive/negative associations due to this bias. Second, we did not perform a replication of the observed association in another sample from Southern Brazil, although our data is in agreement with the majority of studies performed in different populations (5)(6)(7)(8)31,(36)(37)(38)(39)(40) and also with another Brazilian study (23). Third, we only analyzed one SNP in the TCF7L2 gene.…”
Section: Discussionsupporting
confidence: 41%
“…The consistency in the data showing the association between TCF7L2 gene variants and risk for T2DM reported by many studies in different populations is believed to be a reliable indicative of a universal contribution of this gene to T2DM development (31), even though some studies have reported weak or no association with the disease, mainly in Asian populations (21,(32)(33)(34)(35). Thus, to date, around 10 meta-analyses evaluated the pooled effect of TCF7L2 rs7903146 SNP in T2DM risk (5)(6)(7)(8)31,(36)(37)(38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…Single-nucleotide polymorphism rs3792267polymorphism in CAPN10 has been examined on the effect of regulating insulin sensitivity and CAPN10 mRNA levels [33]. However, divergent results were reported and gave a heterogeneous picture owing to racial or regional differences [31,32,34,35]. Our study revealed that the A allele of rs3792267 of CAPN10 was significantly associated with T2DM in Uyghur participants (P = 0.002, adjusted for age, gender and BMI) ( Table 2).…”
Section: Study Findingsmentioning
confidence: 71%
“…Among the 13 T2DM genetic susceptibility loci screened, we found significant association with T2DM for three of them, i.e., rs3792267 (CAPN10), rs1501299 (APM1) and rs3760776 (FUT6). CAPN10 gene, identified as the first susceptibility gene for T2DM by positional cloning [25], has been associated the increased risk of T2DM in different populations [30][31][32]. It has been well documented that the abnormal expression of CAPN10 in pancreatic islets, muscle and liver is related to insulin secretion and action, and thereby is considered to be an important novel pathway involved in glucose metabolism [25].…”
Section: Study Findingsmentioning
confidence: 99%
“…The peroxisome proliferator-activated receptor gamma (PPARG), an important transcription factor, keep the balance of energy metabolism by promoting either energy dissipation or energy deposition [7]. Recent studies reported that PPARG gene was correlated with higher risk to diabetes [8] and the G allele of the rs1801282 C>G polymorphism in PPARG gene was associated with T2DM rsk in a genome-wide association study (GWAS) [9] and has been replicated in some case-control studies; however, other studes found no association between this polymorphism and T2DM [1012]. The peroxisome proliferator-activated receptor gamma co-activator 1 (PPARGC1) family (e.g.…”
Section: Introductionmentioning
confidence: 99%